2012
DOI: 10.1590/s1415-43662012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Produção e nutrientes minerais de milheto forrageiro e sorgo sudão adubado com soro de leite

Abstract: R ESU M OEste estudo objetivou avaliar o desenvolvimento e teores de macronutrientes presentes no milheto e no sorgo Sudão, em resposta à aplicação de doses de soro de leite ao solo. O experimento foi conduzido com solo em vasos com capacidade de 8 dm 3 em ambiente protegido utilizando-se delineamento inteiramente casualizado em arranjo fatorial 2 (aplicação única e parcelada) × 5 (doses de soro) com quatro repetições. As doses foram equivalentes a: 0, 167, 333, 667 e 1000 m 3 ha -1 de soro de leite, determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…Nas avaliações do uso agrícola do soro de leite predominam efeitos benéficos nos solos e respostas positivas das culturas porém as doses empregadas são muito variáveis e não obedecem regras definidas (Gheri et al, 2003;Morrill et al, 2012;Queiroz, 2013). Neste contexto o objetivo do presente trabalho foi avaliar o efeito do soro ácido de leite em atributos químicos do solo, na produção de matéria seca e no acúmulo de nutrientes na parte aérea de milho.…”
Section: Introductionunclassified
“…Nas avaliações do uso agrícola do soro de leite predominam efeitos benéficos nos solos e respostas positivas das culturas porém as doses empregadas são muito variáveis e não obedecem regras definidas (Gheri et al, 2003;Morrill et al, 2012;Queiroz, 2013). Neste contexto o objetivo do presente trabalho foi avaliar o efeito do soro ácido de leite em atributos químicos do solo, na produção de matéria seca e no acúmulo de nutrientes na parte aérea de milho.…”
Section: Introductionunclassified
“…Evaluating the development, yield and contents of macronutrients in millet and Sudan grass, subjected to the application of doses of whey in the soil, Morrill et al (2012) obtained P values superior to those in the control, and adequate for corn (2.5 to 3.5 g kg -1 ) and sorghum (4.0 to 8.0 g kg -1 ), according to IPA (2008). Erthal et al (2010), studying the application of cattle-raising wastewater in the soil, observed that the P contents in the evaluated forages (Tifton 85 grass and black oat) was superior to that obtained in the control.…”
Section: Resultsmentioning
confidence: 99%
“…Sorghum forage was the most commonly used (98.86%) method of silage production employed by the surveyed properties. According to Morrill et al (2012), sorghum is a rustic, fast-growing grass, and is widely used in various forms around the world. According to Cysne and Pitombeira (2012), sorghum has xerophilic characteristics, which include high tolerance of abiotic factors such as drought stress and salinity, and a low demand for mineral nutrients from the soil.…”
Section: Resultsmentioning
confidence: 99%